2020
DOI: 10.2147/ndt.s231877
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effectiveness of a Mindfulness-Based Psychoeducation Programme for Emotional Regulation in Individuals with Schizophrenia Spectrum Disorders: A Pilot Randomised Controlled Trial</p>

Abstract: Background: Emotion dysregulation has emerged as a transdiagnostic factor that potentially exacerbates the risk of early-onset, maintenance, and relapse of psychosis. Mindfulness is described as the awareness that emerges from paying attention to the present moment without judgment. It gently pulls the mind out of the negative emotions induced by the disparity between expectation and reality by focusing on the present moment, instead of worrying about the future or regretting the past. However, only a few rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 84 publications
0
21
0
Order By: Relevance
“…In particular, mood disorders seem to negatively affect physical and psychological response to treatment in chronic patients ( Marazziti et al, 2008 ; Mula et al, 2008 ; Dell’Osso et al, 2012 ; Piccinni et al, 2012 ; Veltri et al, 2012 ; Martino et al, 2019c , 2020b ). Recent studies demonstrated that mindfulness disposition is related to anxiety and depression and this is observable among different clinical populations ( Idusohan-Moizer et al, 2015 ; Zhang et al, 2015 ; Lam et al, 2020 ). Several systematic reviews and meta-analyses showed significant beneficial effects on depressive and anxiety symptoms in patients treated with mindfulness-based interventions ( Strauss et al, 2014 ; Chu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, mood disorders seem to negatively affect physical and psychological response to treatment in chronic patients ( Marazziti et al, 2008 ; Mula et al, 2008 ; Dell’Osso et al, 2012 ; Piccinni et al, 2012 ; Veltri et al, 2012 ; Martino et al, 2019c , 2020b ). Recent studies demonstrated that mindfulness disposition is related to anxiety and depression and this is observable among different clinical populations ( Idusohan-Moizer et al, 2015 ; Zhang et al, 2015 ; Lam et al, 2020 ). Several systematic reviews and meta-analyses showed significant beneficial effects on depressive and anxiety symptoms in patients treated with mindfulness-based interventions ( Strauss et al, 2014 ; Chu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This technique works at an emotional level (triggering a series of biological processes). It is widely suggested for the treatment of pathologies such as stress and anxiety and is a useful tool for confronting the limitations that generate states of depression, anxiety, or stress [ 141 , 142 , 143 ]. As college students are very susceptible to high health-risk behaviours, a recent work [ 144 ] demonstrated that mindfulness-based intervention has valuable effects in both improving mindfulness and reducing many such behaviours.…”
Section: Learning Stimulation Based On Neuroscientific Findingsmentioning
confidence: 99%
“…29,32,40 Current evidence suggests that mindfulness practice, which cultivates both state and dispositional mindfulness in people with SSDs, could improve emotional and psychotic symptoms. [41][42][43][44] Recent randomised control studies and metaanalyses showed that mindfulness-based interventions significantly improved DM, negative emotions, positive symptoms and negative symptoms compared with control groups. [43][44][45][46][47][48][49] A 2-year longitudinal follow-up study of the relationships between changes in the five facets of mindfulness (observing, describing, acting with awareness, nonjudging and nonreactivity) and the clinical outcomes of psychotic patients who received mindfulness training revealed that all facets of mindfulness significantly increased over time and that two facets (observing and acting with awareness) were significantly associated with improvements in positive and negative symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44] Recent randomised control studies and metaanalyses showed that mindfulness-based interventions significantly improved DM, negative emotions, positive symptoms and negative symptoms compared with control groups. [43][44][45][46][47][48][49] A 2-year longitudinal follow-up study of the relationships between changes in the five facets of mindfulness (observing, describing, acting with awareness, nonjudging and nonreactivity) and the clinical outcomes of psychotic patients who received mindfulness training revealed that all facets of mindfulness significantly increased over time and that two facets (observing and acting with awareness) were significantly associated with improvements in positive and negative symptoms. 50 A recent mediation analysis also suggested that negative emotion might mediate the relationship between DM and clinical outcomes, such as quality of life, in people with SSDs.…”
Section: Introductionmentioning
confidence: 99%